Exploring Attitudes of People Towards Polygamous Marriages: A Qualitative Analysis in District Battagram, Pakistan - Fakhr Ud Din; Rafeeuddin; Shakeel Ahmad; Shoukat Nawaz; Tayyaba Noor Qureshi (Review Journal of Social Psychology & Social Works, 2025)
The aim of this study was to empirically investigate the attitudes of people towards polygamous marriages in District Battagram of Khyber Pakhtunkhwa Province of Pakistan. Polygamous marriage is a family pattern, and marital arrangements in which one spouse simultaneously keeps several partners of an opposite sex are known as polygamy. In the current study, the qualitative research paradigm was employed, purposive sampling was used, and a total 40 participants, both male and female from various backgrounds were interviewed using semi-structures interviews (SSIs) based on the principle of data saturation. In order to conduct a thorough analysis of the problem, data was gathered using additional tool like Focused Group Discussions (FGDs). The Braun and Clarke model (2006) proposed a six-step methodology for thematic analysis of the gathered data. The results clearly pointed out that religious beliefs constituted the major reason as to why polygamous marriages were practiced. The economic factors, as a result, became a top issue identified as respondents said that most of the time, being able to cater for multiple households puts a financial squeeze. The culture and social pressure play a very vital role in encouraging polygamy, and we have some who see it as being trendy while others see it as being an issue of old ages. Adjustment to polygamous relationships created tensions between co-wives and stress on children. Some young people began to criticize the continuation of polygamous practices and values in present society owing to changes in education standards. This research establishes that the residents of District Battagram hold diverse views towards polygamy due to religion, economic conditions, emotion, and social issues irrespective of traditional trends, while the new generation’s perspective appears likely to reduce the tolerance towards polygamy. On this basis, the following recommendations are made: the government should pass a law legalizing polygamous marriage provided that it meets this requirement. For wives’ and children’s protection, as well as the sake of the society, these rules in subject should aim at controlling polygamous partnerships. That is why society should also be informed about the existence of polygamous relationships and other consequences of polygamy in general.